2010
DOI: 10.2340/16501977-0564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neuromuscular electrical stimulation on muscle layer thickness of knee extensor muscles in intensive care unit patients: a pilot study

Abstract: Neuromuscular electrical stimulation appears to be a useful adjunct to revert muscle wasting in intensive care unit long-term patients; however, larger studies with a larger sample size are needed to confirm these promising, but preliminary, results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
159
0
29

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(195 citation statements)
references
References 29 publications
4
159
0
29
Order By: Relevance
“…In non-ICU patient populations, EMS has been shown to increase muscle strength and exercise tolerance (637). Preliminary results in small samples of critically ill patients were promising and found that EMS preserved muscle mass (237,272,474), reduced muscle catabolism (73), and exerted shortterm systemic microcirculatory effects (238). In another eight patients with septic shock however, 7 days of EMS did not preserve muscle volume (555).…”
Section: Electrical Muscle Stimulationmentioning
confidence: 92%
“…In non-ICU patient populations, EMS has been shown to increase muscle strength and exercise tolerance (637). Preliminary results in small samples of critically ill patients were promising and found that EMS preserved muscle mass (237,272,474), reduced muscle catabolism (73), and exerted shortterm systemic microcirculatory effects (238). In another eight patients with septic shock however, 7 days of EMS did not preserve muscle volume (555).…”
Section: Electrical Muscle Stimulationmentioning
confidence: 92%
“…Prolonged application of NMES has been reported to attenuate the loss of muscle mass and/or strength in patients recovering from surgery (60,66,69), patients suffering from severe cardiovascular complications (6,58,67), or patients treated in the intensive care unit (25,32). Despite the proposed benefits of NMES in a clinical setting, there is little evidence for the proposed impact of NMES on muscle protein synthesis (27,28).…”
mentioning
confidence: 99%
“…В этом аспекте интересно исследование W. Gruther и соавт. [39], в котором изучали эффекты ЭСМ, помимо групп пассивных тренировок и контроля, также и у пациентов, которые находились в ОРИТ в течение различного времени -менее 7 и более 14 дней. После курса ЭСМ у пациентов, находившихся на момент начала пассивных тренировок менее 7 дней, не бы-ло отличий в толщине мышечного слоя (p=0,457) по срав-нению с группой контроля.…”
Section: клинические и научные перспективы дальнейшего использования unclassified
“…Напротив, у пациентов, находившихся в ОРИТ более 2 нед, в результате ЭСМ мышечный слой был боль-ше в группе пассивных тренировок по сравнению с груп-пой контроля. Кроме того, отмечена значимая динамика толщины мышечного слоя до и после ЭСМ (p=0,036), в то время как в контрольной группе она осталась неизменной (p=0,162) [39]. K. Iwatsu и соавт.…”
Section: клинические и научные перспективы дальнейшего использования unclassified